The Analysis of Circumfix (ka-an) in Minang Language Subdistrict Sei Geringging Pariaman - Adrallisman Adrallisman (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2021)
The aim of the research is to give the description of circumfix ( ka-an) in Minang Language subdistrict Sei Geringging Pariaman. This is descriptive qualitative research. The steps in collecting data are: reading and underlying sentences that contains affixes and classifying the class. The collected data are analyzed by using morphological theory by Bauer (1988). The result of the analysis reveals that circumfix (ka-an) in Minang Language subdistrict Sei Geringging Pariaman could be used with the base form of noun, verb and adjective. Some of them change the class of words (derrivational) and some of them keep the same class of word (inflectional).